The interjection of ômma in the Acehnese language: A natural semantic metalanguage approach - Rostina Taib; Mulyadi Mulyadi (Studies in English Language and Education, 2022)
This paper examines the interjection of ômma in Acehnese language using a natural semantic metalanguage approach. The study employed a qualitative method using oral, written, and artificial data sources. Twelve qualified informants from three study locations, i.e., Aceh Besar, West Aceh, and South Aceh provided their consent to participate in this study. Meanwhile, written data were sourced from Acehnese books and previous studies, and the artificial data were used as complementary to oral and written data. The data analysis is presented using a distributional approach. In addition, the Natural Semantic Metalanguage (NSM) theory was also applied. The results show that the interjection of ômma in the Acehnese language expressed three semantic aspects, i.e., emotive, volitive, and cognitive. The emotive aspect includes expressions of amazement, surprise, and anger. In addition, the meanings of the interjection of ômma are highly dependent on the text and the context of the sentence. A chuckle of amazement, pleasant facial expression, hand-clap, head-shake, or thumbs-up accompanies the interjection of ômma expressing amazement. The interjection of ômma that expresses anger is accompanied by a sour facial expression, such as frowns and lip-biting, as well as a high intonation voice. In expressing a feeling of surprise, the interjection of ômma is accompanied by a voice that indicates joy and a happy facial expression. Meanwhile, the interjection of ômma expressing volition is accompanied by limb movements, either using hands, mouth, or face. The interjection of ômma that expresses the cognitive aspect is followed by movements or pats on the forehead or legs.